COMPARISON OF CALCULATED PREDICTION MODEL RESULTS WITH EXPERIMENTAL STRENGTHS OF CARBON NANOTUBE REINFORCED ALUMINUM MATRIX COMPOSITE MATERIALS - Kucukyildirim, Bedri Onur; Eker, Aysegul Akdogan (YILDIZ TECHNICAL UNIV, 2012)
Industrial type multi-wall carbon nanotube reinforced aluminum matrix composites are successfully fabricated by vacuum assisted infiltration of molten aluminum alloy into the carbon nanotube containing preform. Compressive mechanical properties of these composites are investigated and compared with the calculation results of aforementioned prediction models. Thermal mismatch model is the most matching model for the yield strength of composites due to consideration of thermal expansion differences between reinforcement and matrix material in the model which affects punching of dislocations in the matrix. Furthermore, shear lag model gives the closest results for the ultimate compressive strength values by considering interfacial bonding parameters.
Keywords: Carbon nanotubes; metal matrix composites; shear lag; thermal mismatch; Halpin-Tsai equations; Engineering